Kinesiophobia and Fear Avoidance in Older Adults: A Systematic Review on Constructs and Related Measures. Issue 4 (5th October 2022) - Alpalhão, Vanessa; Cordeiro, Nuno; Pezarat-Correia, Pedro
Abstract : Background and Purpose: In light of the fear avoidance model, kinesiophobia and fear avoidance (FA) can lead to physical inactivity and disability. Previous studies regarding kinesiophobia and FA in older adults have reported conflicting results. The purpose of this review was to identify the reported constructs and assessment instruments used in published studies on kinesiophobia and FA in older adults and to verify the alignment between the instruments used and the constructs under study. Methods: Following the Preferred Reporting Items for Systematic reviews and Meta-Analyses 2020 statement (PRISMA-2020), 4 databases were searched from January 2005 to March 2020. All study types, except qualitative, were eligible for inclusion. The participants were 65 years and older. Studies were excluded in the absence of sufficient data on participant age. Study characteristics, constructs related to kinesiophobia, fear and/or avoidance, and instruments used were extracted independently by 2 reviewers. Results: Fourteen articles were selected for inclusion in the study, in which 7 constructs were identified. The most reported constructs were "fear avoidance beliefs" (FAB) (50%; n = 7), "kinesiophobia" (35.7%; n = 5), and "fear of falling" (14.3%; n = 2). The remaining constructs were only approached, each in 7.1% (n = 1) of the included studies. Seven instruments were used to assess the constructs. The Fear Avoidance Beliefs Questionnaire (FABQ) was the most used instrument (n = 3) to evaluate "FAB, " and the Tampa Scale for Kinesiophobia-11 (TSK-11) was the most reported (n = 3) to assess "kinesiophobia." Conclusion: This review identified a large diversity in the constructs and instruments used to study kinesiophobia and FA among older adults. Some constructs are used interchangeably although they do not share the same conceptual definition. There is poor standardization in the use of assessment tools in accordance with the construct under study. Clinical evaluation and study results can be biased owing to this ambiguity.